2017
DOI: 10.1080/09542299.2017.1352460
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and release characteristics of nitrogen fractions in sediments in the estuaries of Dianchi Lake, China

Abstract: Columnar sediment samples were collected from five representative estuaries of Dianchi Lake, China. And the vertical distribution of each fraction of nitrogen (IEF-N, CF-N, IMOF-N, OSF-N) were tested. The results showed that the TN content in sediments from areas A, B, C, D and E gradually decreased with depth between 0 and 15 cm, then sharply decreased with depth between 15 and 30 cm and stabilized at depth below 30 cm, indicating the exogenous input of N in these areas has not been controlled effectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The water quality and eutrophication status of a lake will deteriorate when the pollution loading into the lake exceeds the carrying capacity of the water environment [12,13]. Moreover, climate changes accompanied by rising air temperatures and changes in wind speed and direction can indirectly affect the water temperature structures of lakes and change the hydrodynamic conditions in shallow lakes to accelerate the occurrence of water pollution and toxic cyanobacterial blooms, which are the key characteristics of eutrophication [3,10,14,15]. All water quality problems will degrade the stability of lake ecosystems and landscape values, reduce water functions, and lead to the reduction in available water resources, even causing irreversible harm to human health [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water quality and eutrophication status of a lake will deteriorate when the pollution loading into the lake exceeds the carrying capacity of the water environment [12,13]. Moreover, climate changes accompanied by rising air temperatures and changes in wind speed and direction can indirectly affect the water temperature structures of lakes and change the hydrodynamic conditions in shallow lakes to accelerate the occurrence of water pollution and toxic cyanobacterial blooms, which are the key characteristics of eutrophication [3,10,14,15]. All water quality problems will degrade the stability of lake ecosystems and landscape values, reduce water functions, and lead to the reduction in available water resources, even causing irreversible harm to human health [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Since China’s economic reform and its integration with the world economy in the early 1980s, the country experienced a dramatic change regarding its social development and economy. Moreover, the natural environment in China suffered from accelerated lake eutrophication, and the eutrophication in Lake Dianchi is considered the most serious [15,35]. By the end of the 1990s, more than 70% of the lakes were considered eutrophic, and this phenomenon has become even more severe in recent years [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the corresponding overlying water was also collected and the parameters including temperature, pH value, oxidation-reduction potential (E h ), dissolved oxygen (DO) were measured in the field. The properties of those studied sediments and overlying water were also reported in our previous studies [15]. The TN, TP, and soluble reactive P (SRP) within the overlying water were measured in the laboratory [16].…”
Section: Study Area Sediment Sampling and Overlying Water Characterimentioning
confidence: 99%
“…The contribution of nitrogen to water eutrophication has increased significant interest among scientists, and a large number of studies have confirmed that nitrogen is another key limiting factor in the water eutrophication of freshwater lakes (Han et al, 2014;Shan et al, 2015). At present, most scholars have mainly focused on the influences of the lake water body sediment nitrogen composition, occurrence forms, spatial distribution, diffusion flux, and interface structure on the contribution to the water environment (Pennuto et al, 2014;Yang et al, 2017). Conversely, little research has been conducted on the nitrogen release from sediments, which is affected by changes in the overlying water environment.…”
Section: Introductionmentioning
confidence: 99%